The encyclopedia of games (London : Aurum Press, 1998)
Whether you are looking for a quiet game of Patience, or a party game that can absorb the energies of a houseful of children, or for a game that will liven up a dinner party, you will find what you need in this book.
Includes bibliographical references (p. 291-293) and index
Keywords: Games -- Encyclopedias; Indoor games -- Encyclopedias; Board games -- Encyclopedias